Critical Thinking Instruction - et. al., Raximova Mexribon, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study sought to investigate EFL learners` attitudes towards critical thinking (CT) instruction. To this end, based on the result of an Oxford Placement Test, thirty intermediate EFL learners were selected from among 90 participants to take part in this study at a language institute. A repeated measure design was utilized by the researchers based on which the same group of participants took part in the control and experimental phases of the study. At the end of the experiment, the participating EFL learners answered an open-ended researcher-made questionnaire the items of which were based on existing literature in order to explore the participants` views and attitudes towards the type of instruction offered to promote their CT skills. It was found that more than two-third of the participants were interested in using CT skills at class. The findings have some implications for course designers, material developers, and teachers to introduce and foster CT skills in classrooms for students.